LEKSIKON REMPAH RATUS PARAM PADA MASYARAKAT MELAYU SAMBAS DI DESA SARANG BURUNG KUALA - Ghozali, Fajrin; Heryana, Nanang; Syahrani, Agus (Universitas Tanjungpura, 2023)
This study aims to describe and analyze the spice hundreds param lexicon in the Malay Sambas community in Sarang Burung Kuala Village. The research method used in this study is a descriptive method with a qualitative research form. Sources of data in this study directly from informants. The data obtained in this study resulted in 92 hundred param spice lexicons in the Sambas Malay community in Sarang Burung Kuala Village, consisting of 10 param types, 48 lexicons for spices or medicinal ingredients, 18 lexicons for tools used, there are 9 lexicons for how to make them, and based on how to use them there are 7 lexicons. The form of the spice hundreds param lexicon in the Malay Sambas community in Sarang Burung Kuala Village is in the form of monomorphemic lexicons totaling 27, polymorphemis totaling 21 lexicons, and phrases totaling 44 lexicons. The meaning of the spice hundreds param lexicon in the Malay Sambas community in Sarang Burung Kuala Village based on lexical meanings totals 92 lexicons and 12 lexicons for cultural meanings. The form of an Indonesian language learning text based on the spice hundreds param lexicon for the Malay Sambas community in Sarang Burung Kuala Village is a procedure text.